Typical tests on cold-formed steel structures - Md. Tahir, Mahmood; Tan, Cher Siang; Shek, Poi Ngian (2006)
Cold-formed steel has been recently brought into Malaysian construction. It is a steelwork technology that has high potential to be developed in Malaysia, that can offers advantages such as fast erection, lightweight, clean and easier construction. This paper reported a series of research studies carried out in UTM for locally produced coldformed steel sections and roof truss system. The research work included study on the member capacities for lipped C-section and Hat-section, a full-scale test for roof truss system and the cold-formed steel tek-screw connection capacities. All the studies were based on the requirements of British Standard BS 5950 Part 5 1998. The actual capacities of the proposed sections were ratio from 1.09 - 2.21 compared to the design strength. The full-scale experimental test on roof truss also achieved two times of the estimated design capacities. The tek-screw connection capacities in resistance to shear force and pull-out force ranged 76% - 141% higher than the design requirements. The connection also withstand 10000 times of dynamic load that verified its performance in long-term serviceability. The results of the experimental tests on the proposed cold-formed steel section and roof truss system showed good agreement to the requirements of BS5950 Part 5 1998.